The Rise of Cosmetic Gynecological Surgeries in Pakistan: Navigating Cultural Sensitivity and Patient Safety - Ahmad, Saqib (Journal of University College of Medicine and Dentistry, 2024)
As cosmetic gynaecological procedures become more popular in Pakistan, it is important to evaluate their impact on the healthcare system. Many women pursue these surgeries to enhance their self-esteem, improve sexual gratification, or gain social acceptance. However, these motivations often conflict with traditional values of femininity and modesty in Pakistan, presenting unique challenges. Additionally, the lack of regulation in the field is a significant concern. Many surgeries are performed in unregulated clinics, which can lead to risks such as infections, scarring, and psychological distress. Therefore, it is essential for healthcare providers to ensure that these surgeries are conducted in accredited facilities by qualified practitioners.